To what extent can community energy mitigate energy poverty in Germany? - Bode, Annika (Frontiers in Sustainable Cities, 2022)
The reduction of energy poverty and the expansion of citizen-led community energy projects are two important issues for a just energy transition in the European Union. While some socio-economic aspects of community energy are well researched, there is a dearth of literature on its potential to include vulnerable households and eventually reduce the risk of energy poverty. Through the lens of energy vulnerability thinking, this paper examines current and future drivers of energy poverty in Germany, as well as factors that may limit or facilitate the inclusion of vulnerable consumers in community energy. It draws on previous studies and on 12 semi-structured interviews conducted in the Summer of 2021 with experts in the fields of energy poverty or community energy. Using a three-tenet conceptualization of energy justice, the article argues that community energy projects can mitigate energy poverty in Germany by providing affordable renewable electricity to vulnerable and energy-poor consumers, as well as by establishing fair procedures that consider various vulnerability contexts. Yet, deep-rooted distributional injustices in housing and social transfer schemes that drive energy poverty are likely to remain. In order to advance energy justice, community energy projects hinge on a collaborative multi-level and multi-actor environment.